Fano polytopes - Kasprzyk, Alexander M.; Nill, Benjamin (World Scientific, 2013)
Fano polytopes are the convex-geometric objects corresponding to toric Fano varieties. We give a brief survey of classification results for different classes of Fano polytopes.